The task of controlling the aircraft - Казак, В. М.; Боярінов, І. В.; Боярінова, Ю. Є. (Proceedings of National Aviation University (archive), 2020)
The problem of controlling the motion of an aircraft from general functional positions is considered. The necessity of including in the statement of the problem the requirements of minimization of the stabilizing functional is substantiated. The criterion of optimum speed, criterion of a minimum of energy expenses on a control and their combination is offered